2012
DOI: 10.1038/ejhg.2012.146
|View full text |Cite
|
Sign up to set email alerts
|

A novel LRSAM1 mutation is associated with autosomal dominant axonal Charcot-Marie-Tooth disease

Abstract: Charcot-Marie-Tooth (CMT) disease is the most common hereditary neuropathy resulting from mutations in 430 genes expressed in either the Schwann cells or the axon of peripheral nerves. The disease is classified into demyelinating (CMT1), axonal (CMT2) or intermediate (CMTI) based on electrophysiological and pathological findings. Our study focused on the identification of a novel disease mutation in a large Sardinian family with CMT2 of autosomal dominant (AD) inheritance. All available family members were cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…Recently, members of our group identified a frameshift mutation in LRSAM1 as the cause of dominantly inherited, axonal sensorimotor neuropathy in a Dutch family (Charcot–Marie–Tooth, CMT, type 2P) 1. This finding was confirmed by others,2, 3 and another homozygous mutation in this gene was previously found in a recessive CMT family (AR‐CMT2P) 4. In the original paper on the Dutch family, the clinical description incidentally mentioned that two of the affected members showed signs of Parkinson's disease (PD).…”
Section: Introductionsupporting
confidence: 67%
“…Recently, members of our group identified a frameshift mutation in LRSAM1 as the cause of dominantly inherited, axonal sensorimotor neuropathy in a Dutch family (Charcot–Marie–Tooth, CMT, type 2P) 1. This finding was confirmed by others,2, 3 and another homozygous mutation in this gene was previously found in a recessive CMT family (AR‐CMT2P) 4. In the original paper on the Dutch family, the clinical description incidentally mentioned that two of the affected members showed signs of Parkinson's disease (PD).…”
Section: Introductionsupporting
confidence: 67%
“…Homozygosity mapping yielded a splice site mutation c.1913-1G >A in the LRSAM1 gene giving rise to a premature stop codon 20 bp inside the penultimate exon. Subsequently, two further mutations in LRSAM1 were identified in a Dutch and a Sardinian family with dominant axonal CMT [8,9]. In both studies, the clinical and electrophysiological findings were very similar to that reported by Guernsey et al [7].…”
Section: Introductionsupporting
confidence: 63%
“…Consistent with this idea, the mutant protein could be detected in blood cells of heterozygous mutation carriers in one family [9]. It is tempting to speculate that such a dominant negative effect results immediately from the disruption of the RING domain, where all three mutations occur (Table 2).…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, it was deduced that PHF23 may exert antagonistic effects on LRSAM1 in normal physiological conditions. In view of the functional multiplicity of LRSAM1 on anti-infection, 13 Charcot-Marie-Tooth disease, [15][16][17] and colorectal cancer, 19 whether PHF23 is involved in these diseases deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reports indicate that mutations of LRSAM1 cause Charcot-Marie-Tooth disease. [15][16][17] Loss of LRSAM1 increases the sensitivity of peripheral axon degeneration in a mouse model of Charcot-Marie-Tooth disease, 18 indicating that dysregulation of LRSAM1 is implicated in neuronal development and homeostasis. A recent finding indicates that the level of LRSAM1 is significantly upregulated in patients with colorectal cancer, 19 implying that the aberrant expression of LRSAM1 may be involved in the cancer process.…”
Section: Introductionmentioning
confidence: 99%